2015
DOI: 10.1111/cge.12677
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genetic testing with ethnic‐specific filtering by allele frequency in a Japanese hearing‐loss population

Abstract: Recent advances in targeted genomic enrichment with massively parallel sequencing (TGE+MPS) have made comprehensive genetic testing for non-syndromic hearing loss (NSHL) possible. After excluding NSHL subjects with causative mutations in GJB2 and the MT-RNR1 (1555A>G) variant by Sanger sequencing, we completed TGE+MPS on 194 probands with presumed NSHL identified across Japan. We used both publicly available minor allele frequency (MAF) datasets and ethnic-specific MAF filtering against an in-house database of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
0
27
2
Order By: Relevance
“…We focused on the pathogenicity of each CDH23 allele, which were determined by their ethnic-specific MAF in our composite cohort (adult control cohort) (S1 Fig) [24, 25]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on the pathogenicity of each CDH23 allele, which were determined by their ethnic-specific MAF in our composite cohort (adult control cohort) (S1 Fig) [24, 25]. …”
Section: Resultsmentioning
confidence: 99%
“…CDH23 variants were not detected in the 200 normal control chromosomes (< 0.005) from our institute, which was a proposed ethnicity-specific MAF with a cut-off threshold (0.005) for autosomal recessive pathogenic variants [24, 25]. …”
Section: Methodsmentioning
confidence: 92%
“…CNV analysis of MPS data has resulted in the identification of several novel CNVs [23*, 25, 31, 32*, 49, 54*] and has shown that many genes can harbor CNVs. Comprehensive CNV detection is as important as comprehensive SNV detection and analysis and must be included in all analytic pipelines.…”
Section: Cnv Inclusion and Methodologymentioning
confidence: 99%
“…Moteki and colleagues diagnosed 27% of 194 probands in a GJB2 -negative Japanese cohort. Their diagnoses included 20 genes and they estimated a diagnostic rate of 40% if they had not preselected their patient population [25]. They also provided an in-depth phenotypic analysis that adds to our knowledge of the clinical presentation associated with several genes, including LRTOMT, P2RX2, POU3F4, PTPRQ , and USH2A [2630].…”
Section: Diagnostic Ratementioning
confidence: 99%
See 1 more Smart Citation